Core Concepts in Renal Transplantation - Chandraker, Anil; Sayegh, Mohamed H.; Singh, Ajay K. (Springer US, 2012)
Though kidney transplantation is considered a routine procedure, there are still significant challenges in post-transplant management. Core Concepts in Renal Transplantation is a clinically focused authoritative guide to the management of kidney transplantation.  This comprehensive, state-of-the-art reference summarizes the recent changes in the field of transplantation, offering the complete range of up-to-date information on all the various aspects of basic immunobiology and the medical care of the transplant recipient.  Written by a team of renowned authorities in renal transplantation, this concise resource is intended for both the nephrologist and the non-specialist with an interest in kidney transplantation